2017
DOI: 10.21273/hortsci11707-16
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Oxygenation Techniques and the Chlorophyll Responses of Pelargonium tomentosum Grown in Deep Water Culture Hydroponics

Abstract: Pelargonium tomentosum Jacq.; the peppermint-scented pelargonium, is an herbaceous groundcover indigenous to the Western Cape of South Africa. Volatile oils are produced by this plant, which are used in the fragrance industry. Studies on other Pelargonium species have shown chlorophyll content may affect the yield of essential oils. This study was carried out to investigate the viability of growing P. tomentosum in deep wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The treatment with 5 mM H 2 O 2 appeared healthier than those of the control and exhibited a higher total chlorophyll content (2.25 -2.9) fold in comparison to that of untreated trees in both seasons. Similar positive effects of H 2 O 2 chlorophyll content were reported by Butcher et al (2017) in pelargonium tomentosum and Khandaker et al (2012) in wax apple…”
Section: Total Chlorophyllsupporting
confidence: 82%
“…The treatment with 5 mM H 2 O 2 appeared healthier than those of the control and exhibited a higher total chlorophyll content (2.25 -2.9) fold in comparison to that of untreated trees in both seasons. Similar positive effects of H 2 O 2 chlorophyll content were reported by Butcher et al (2017) in pelargonium tomentosum and Khandaker et al (2012) in wax apple…”
Section: Total Chlorophyllsupporting
confidence: 82%
“…Similarly, significant variability was observed in the chlorophyll content of Zea mays and Sorghum bicolour cultivated in soils amended with organic and inorganic fertilisers (Amujoyegbe et al 2007). Although outside the scope of this research, a combination of an airpump, high-frequency H 2 O 2 application, and vortex oxygenation was reported to have yielded the highest mean value of chlorophyll in Pelargonium tomentosum (Chen et al 2010;Butcher et al 2017), suggesting that oxygenation may drive photosynthesis through increased chlorophyll production. Findings from this research, therefore, corroborate what has been reported in earlier literature; that nutrient application increases chlorophyll content.…”
Section: Discussionmentioning
confidence: 62%
“…In this system, the growth medium is made up of Styrofoam, which floats directly on the nutrient solution. Oxygen delivery is the difficult part of this system [13]. Since the plants' roots are completely submerged in the nutrients a system of air pump and air stone provides them with oxygen.…”
Section: Deep Water Culture (Dwc) Hydroponicsmentioning
confidence: 99%